A utilização de indicadores de contexto na análise de eventos de saúde - Amelia Augusta de Lima Friche (2011)
Introduction: The idea that the place where we live, in addition to individual characteristics, contributes to outcomes related to health has motivated the implementation of many epidemiological studies. In this perspective, it becomes critical to understand which dimensions of context affect health as well as how health events behave and are influenced by each of these dimensions. Many studies have used different sources of information to characterize the context: local or national censuses; systematic social observation of the place of residence, geographic information systems, and further information on the perceptions of individuals about their residence place. However, the measurement of the context is complex and presents itself as a challenge. Objective: The overall objective of this thesis was to evaluate the behavior of different context indicators in Belo Horizonte and its association with health-related events from the perspective of Urban Health. Methods: We used two source of individual information from health surveys conducted in Belo Horizonte, the "Household Survey on Risk Behavior and Morbidity of Non-communicable Diseases and Health Problems" (InqDANT) and Saúde em Beagá Study". The contextual indicators used were the Index of Quality of Urban Life (IQVU) and Health Vulnerability Index (SVI). We evaluated the adequacy of IQVU as an indicator of the neighborhood context and its association with health-related events - self-rated health, chronic diseases and functional limitation. We also evaluated the association between the IVS and the presence of functional limitation. From information on individuals' perception of their neighborhood, scales were constructed to represent attributes of neighborhood context and evaluated its psychometric and ecometric properties. Results: As an indicator of context, the IQVU was associated with the presence of functional limitation, but not associated with self-rated health, or the presence of chronic diseases. The IVS discriminated adequately vulnerable population in Belo Horizonte, graduate and confirmed by the positive association found between the presence of functional limitation and residence in areas of greater vulnerability to health. Based on the theoretical model and previous studies, ten scales were built, representing different attributes of the neighborhood - public services, aesthetic quality, walking environment, safety, violence, physical problems, social problems, social cohesion, neighborhood participation and neighborhood problems. All scales showed good psychometric properties and the majority had moderate ecometric properties. Most of the scales were associated with predictors of individual and socioeconomic neighborhood level. Preliminary analysis using the scales as contextual indicators in the multilevel analysis of factors related to functional limitations showed significant associations with the scales of public services, environment, violence, physical disorders and problems in the neighborhood. Conclusion: This study showed progress in identifying and evaluating the use of context indicators available in the city of Belo Horizonte. The IVS and the IQVU presented themselves as good context indicators in the assessment of functional limitation. The scale developed can be used as indicators of multilevel analysis in the context of events related to the "Saúde em Beagá Study." Understanding the relationships between neighborhoods and health, can contribute to support interventions aimed at improving the health of populations living in urban centers